2009
DOI: 10.2116/analsci.25.711
|View full text |Cite
|
Sign up to set email alerts
|

Solid Phase Selective and Extractive Preconcentration of Silver Ion from Aqueous Samples on Modified Silica Gel with 5-(4-Dimethylaminobenzylidene)-Rhodanine; Prepared by Sol-Gel Method

Abstract: A new modified silica gel doped with 5-(4-dimethylaminobenzylidene)-rhodanine was prepared for separation, preconcentration and determination of silver ion by atomic absorption spectrometry. This new modified silica gel was used as an effective adsorbent for the solid phase extraction of Ag + from aqueous solutions. The variables that influence the adsorption/desorption of trace levels of Ag + were optimized in the column process. The preconcentration factor and capacity of the adsorbent at optimum conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The method is simple, accurate, and economical and can be applied for the determination of these ions in environmental samples. The figure of merit of the purposed method is comparable to the other reported methods [39][40][41][42][43][44][45] and additionally, the method has the advantage of environment-friendly. The system showed reproducibility and reliability in analytical data, with an RSD value of lower than 5% on triplicate experiment.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The method is simple, accurate, and economical and can be applied for the determination of these ions in environmental samples. The figure of merit of the purposed method is comparable to the other reported methods [39][40][41][42][43][44][45] and additionally, the method has the advantage of environment-friendly. The system showed reproducibility and reliability in analytical data, with an RSD value of lower than 5% on triplicate experiment.…”
Section: Discussionsupporting
confidence: 53%
“…Since metal ions are generally at very low concentrations in a variety of samples of interest by the detection limit of FAAS, it is important to obtain high enrichment factors [36][37][38][39][40][41][42][43][44][45]. In order to explore the possibility of enriching low concentrations of ions from the large sample volume, the influences of the sample volume on the recovery of metal ions were also investigated.…”
Section: Effect Of Sample Volumementioning
confidence: 99%
“…At pH 1.5‐6, silver ions react with the reagent to form a yellow compound and then turns orange. With the increasing of pH from 7 to 10.5, the color of the reactant turns to blue . When a M 3 grafted film reacted with silver ions at pH 8, it observed that the solution turns from orange to blue while the blank film did not change ( Figure S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…2 Various sorbents such as multi-walled carbon nanotubes (MWCNTs), 3 alumina, 4 activated carbon, 5 polytetrafluoroethylene (PTFE), 6 chelating ions exchange resin 7 and silica gel [8][9][10][11][12][13][14] have been used and studied in SPE. The conventional batch or column procedure for preconcentration based on SPE has proven an effective method, but it is tedious, time-consuming, requires large sample and reagent volume.…”
Section: Introductionmentioning
confidence: 99%